Hubungan Sikap Dan Konsumsi Junk Food Dengan Konsumsi Sayur Dan Buah Mahasiswa Jurusan Gizi (Studi Di Politeknik Kesehatan Kemenkes Banjarmasin) - Aziza, Kamalia Noor; Farhat, Yasir (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Fulfillment of adolescents physiological requires adequate nutrition including fruits and vegetables. However, They tend to choose fast food such as junk food which contains added sugar and fat than consuming vegetables and fruit. According to result of basic health research (Riskesdas) in 2018, the proportion of fruit / vegetable consumption per day in a week for people aged 5 years and over to the Regency / City of South Kalimantan Province, Banjarbaru City has a level of non-consumption reaching 11,79%, 1-2 portions a week reaching 78,96%, 3-4 servings a week reaches 8,64%, and more than 5 servings a week reaches 0,61%. The purpose of this study was to determine the relationship between attitudes and junk food against vegetable and fruit consumption among students majoring in nutrition at the Politeknik Kesehatan Kemenkes Banjarmasin. This type of research is an analytical observational study with a cross sectional approach. The population of this study were 294 students majoring in nutrition at the Health Polytechnic of the Ministry of Health Banjarmasin. Sampling used 83 people with simple random sampling technique. This research was conducted using an online questionnaire with WhatsApp and Google Form. Data analysis using the Spearman Rank correlation test α = 0,05. The results showed the correlation test using the Rank Spearman correlation test found that there was no significant relationship between attitudes and consumption vegetables and fruits and there is a significant relationship between consumption junk food and consumption vegetables and fruit. Keyword : Attitude, Junk Food, Vegetables, Fruit